Pemanfaatan Limbah Cair Cucian Industri Garam Sebagai Mg(OH)2 - Yuliastuti, Rieke; Cahyono, Handaru Bowo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTThe salt industry is one of the sectors that play an important role in Indonesia. The production process involves a washing process to eliminate non-NaCl material content to meet quality standards. However, this stage of the process has an impact on the production of salt washing wastes, which contain a lot of Mg and Na ions. In contrast, Mg from the washing process actually can be used to produce Mg(OH)2Ã‚Â compounds that were widely used in the paper, cement, and pharmaceutical industries. Therefore, this study aims to determine the potential of the remaining water in the salt industry's washing process so that it can be recycled as Mg, especially Mg(OH)2, so that the washing water can be recycled and reused. The method used for Mg recovery is by concentrating, drying, and settling with Ca(OH)2. From the results of the characteristic test using XRD, it is known that the result of Mg in the form of compounds Mg(OH)2Ã‚Â and Mg(O). Quantitatively, the Mg obtained from 1 liter of industrial salt wastewaterÃ‚Â is 3.68 grams.Keywords: brine, Mg, Ca(OH)2, Mg(OH)2ABSTRAKIndustri garam adalah salah satu industri yang memegang peranan penting di Indonesia. Proses produksinya melibatkan proses pencucian untuk mengeliminasi kandungan material non NaCl demi memenuhi ketetapan baku mutu. Namun tahapan proses ini berdampak pada produksi limbah bekas cucian garam yang banyak mengandung ion Mg dan Na. Padahal Mg dalam limbah cucian bisa digunakan untuk produksi senyawa Mg(OH)2Ã‚Â yang banyak digunakan dalam industri kertas, semen, dan farmasi. Oleh karena itu, penelitian ini bertujuan untuk mengetahui potensi air sisa proses cucian industri garam sehingga dapat dimanfaatkan lagi sebagai Mg khususnya Mg(OH)2Ã‚Â sehingga air cucian tersebut tidak terbuang menjadi limbah. Adapun metode yang digunakan untuk recovery Mg adalah dengan pemekatan, penyeringan, dan pengendapan dengan Ca(OH)2. Dari Hasil uji karakteristik menggunakan XRD diketahui bahwa hasil akhir Mg dalam bentuk senyawa Mg(OH)2Ã‚Â dan Mg(O). Secara kuantitatif, Mg yang diperoleh dari 1 liter limbah cair industri garam sebesar 3,68 gram.Kata Kunci :Ã‚Â limbah cucian garam, Mg, Ca(OH)2, Mg(OH)2